Digital Economy In Developing Msmes In Medan City Point Of View Of Islamic Business Ethics - Sri Ramadani; Reni Ria Armayani Hasibuan; Nur Fadhilah Ahmad Hasibuan; Nurhayati Nurhayati (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the potential of the digital economy in the development of Micro, Small, and Medium Enterprises (MSMEs) in Medan City and examine the application of Islamic business ethics in the process of business digitalization. The research method used is descriptive qualitative with in-depth interviews, direct observations, and documentation studies from various relevant sources. The collected data were analyzed thematically to identify patterns, relationships, and factors influencing the adoption of the digital economy among MSME players. The findings indicate that the digital economy holds significant potential in supporting MSME growth in Medan City, as evidenced by the 3,000 MSMEs that have received training and assistance from the government. However, several challenges hinder its implementation, including limited capital, low digital literacy, difficulty accessing information, and a reluctance among business owners to transition to digital systems. From the perspective of Islamic business ethics, economic digitalization is permissible as long as it does not contradict Sharia principles, such as honesty, justice, and transaction transparency. While most MSME players are not fully aware of Islamic business ethics concepts, many have unknowingly applied these values in their business activities. This study provides recommendations for the government and stakeholders to enhance digital literacy and offer continuous support through more flexible regulations, intensive training, and financial incentives to accelerate MSME digitalization based on Islamic business ethics.